ENERGY EFFICIENT LANDSCAPE DESIGN PROPOSALS IN TRABZON CITY CENTER - Demir, Sara; Koc, Seren (Parlar Scientific Publications (P S P), 2018)
The population growth, technological development, unsustainable consumption, disasters and climate changes in urban cities cause to destroy the natural and cultural values, decay the ecological integrity and changes landscape of urban. The increasing trend of urban has been recognized in the international scale and takes into consider the improvement of sustainable energy efficient in recent years. Urban open spaces have important role on human life as a social welfare and on ecological integrity of urban life. Lack of green infrastructure system and unsustainable intensively impermeable construction affected negatively the quality of urban. Therefore, one of the development countries, Turkey, is under pressure because of rapid and unplanned urban growth. Trabzon is one of the big cities of Turkey and it has rapidly grown after declaring as a metropolitan municipality since 2012. Thus, open green areas in urban have turned to intensively construction area and caused to diminish the open spaces. As a result, Trabzon city center needs to increase the green open spaces and control the heat island due to impermeable surfaces. In this context, the aim of this study is to offer sustainable energy efficient methods by designing green infrastructure with water conservation to reduce urban heat effects caused by climate change. To reach our aim, it was developed the street design proposal in Kahramanmaras street of Trabzon city center to create both green open green spaces and collect the rainwater for social, ecological and economic urban life. For this energy efficient design in Kahramanmaras Boulevard, rainwater was collected by green systems, storage and filtering. The green rainwater collector with filtering was best effective way to protect water and increase the healthy green areas by decreasing the intensive vertical and horizontal impermeable surfaces for this study. These street design proposals can set a good example for the other cities under pressure of urban growth and improve social and economic life quality of citizen and ecological integrity of urban landscape by providing urban and environmental balance.
Keywords: Energy efficient; street design; rainwater; water conservation; urban landscape; Trabzon city